Um estudo dos modelos populacionais e aplicações - Melo, Thabata Maria Queiroga de (Universidade Federal de São Carlos, 2021)
The study of population dynamics is an area of science attempted to understand and describe, in a deterministic way, the temporal variations size of biological populations, being also important to “give specific character for the configuration of a society and the pertinent issues of its multiple aspects” (SETI et al., 1999, p.1). Starting from the understanding of how ordinary differential equations are used in mathematical modeling, in this work we enunciate and study the functioning of the population dynamics models of Malthus, Verhulst and Gompertz, complementing with a study of how the applications using the least squares method helps to correct hypothesis and effects in the way that population were described.
A study of population models and applications
Keywords: Dinâmica populacional; Modelagem Matemática; Equações diferenciais ordinárias; Population Dynamics; Mathematical Modeling; Ordinary Differential Equations.; Least Squares; CIENCIAS EXATAS E DA TERRA::MATEMATICA::MATEMATICA APLICADA